The Influence of Knowledge and Skills of Employees Toward Human Resource Information System Performance in Transportation Firm: A Case Study of Aramex Company of Egypt - Abourawi, Ahmed Omran (2008)
This study was to find out whether there is a relationship between knowledge, skill and Human Resource Information System (HRIS) Performance. This study examined the relationship between performances of HRIS in Aramex Company of Egypt. This study is designed to provide the benefit for practitioners, especially for employees and management position in Aramex Company. The study found that there are positive relationship between knowledge, skill and HRIS performance in Aramex Company.